Nanostructured, Functional, and Flexible Materials for Energy Conversion and Storage Systems - Pandikumar, A.; Pandikumar, A.; Rameshkumar, Perumal (Elsevier Science, 2020)
Nanostructured, Functional, and Flexible Materials for Energy Conversion and Storage Systems gathers and reviews developments within the field of nanostructured functional materials towards energy conversion and storage. Contributions from leading research groups involved in interdisciplinary research in the fields of chemistry, physics and materials science and engineering are presented. Chapters dealing with the development of nanostructured materials for energy conversion processes, including oxygen reduction, methanol oxidation, oxygen evolution, hydrogen evolution, formic acid oxidation and solar cells are discussed. The work concludes with a look at the application of nanostructured functional materials in energy storage system, such as supercapacitors and batteries. With its distinguished international team of expert contributors, this book will be an indispensable tool for anyone involved in the field of energy conversion and storage, including materials engineers, scientists and academics. - Covers the importance of energy conversion and storage systems and the application of nanostructured functional materials toward energy-relevant catalytic processes - Discusses the basic principles involved in energy conversion and storage systems - Presents the role of nanostructured functional materials in the current scenario of energy-related research and development